OPTIMALISASI MANAJEMEN MODAL KERJA DAN ARUS KAS UMKM DI KOTA SERANG UNTUK MENINGKATKAN STABILITAS KEUANGAN USAHA - Idayu, Riyanthi; Sari, Diah Permata; Pertiwi, Sari Putri (Indonesian Collaboration Journal of Community Services (ICJCS), 2026)
This community service program aims to optimize working capital management and cash flow of micro, small, and medium enterprises (MSMEs) in Serang City to enhance business financial stability. The activities were conducted for one month in September 2025 using participatory approaches through training, hands-on practice, and intensive mentoring. The program focused on improving financial literacy, systematic transaction recording, cash flow planning, and effective working capital control. The results showed significant improvements in MSMEs’ financial management practices, including increased discipline in bookkeeping, better cash flow control, and clearer separation between personal and business finances. These improvements contributed to enhanced liquidity, timely payment of obligations, and more stable operational funding. Furthermore, the mentoring process encouraged positive managerial behavior changes, enabling MSMEs to make more rational and data-driven financial decisions. Overall, the program successfully strengthened financial resilience, improved business sustainability, and increased the competitiveness of MSMEs in Serang City. The model applied in this program is expected to be replicable in other regions with similar socio-economic characteristics.